PENGARUH EMOSIONAL QUOTIENT, SPIRITUAL QUOTIENT DAN ADVERSITY QUOTIENT TERHADAP KINERJA PEGAWAI POLTEKKES KEMENTERIAN KESEHATAN PALU - Lasman, Kartini (Katalogis, 2018)
The study identifies the influence emosional quotient, spiritual quotient and adversity quotient on the performance of officials in helath polytechnic the ministry of health Palu. The aim of the study is to determine and analyze simultaneous and partial influence emosional quotient, spiritual quotient and adversity quotient on the performance of officials in helath polytechnic the ministry of health Palu. Method of study is descriptive and it distributes 118 questionnaires to respondents. The result indicates that correlation among independent variables of emosional quotient, spiritual quotient and adversity quotient on the performance of officials in helath polytechnic the ministry of health Palu is 0.637, that indicates a strong correlation between independent and dependent variables. Adjusted R square or determinant coefficient (R2), that intended to determine the influence emosional quotient, spiritual quotient and adversity quotient on the performance of officials in helath polytechnic the ministry of health Palu is 0.390 or 39%. This means that the influence of independent variables towards dependent variables is 39% while the remaining of 61% influenced byÂ variables that are not studied.